Data access control policy of encrypted deduplication system - Chunfu JIA; Guanxiong HA; Ruiqi LI (Tongxin xuebao)
To solve the problem that convergent encryption was commonly used in existing encrypted deduplication systems in cloud storage and data owner couldn’t effectively enforce access control on their outsourced data,an encrypted deduplication system was proposed to support access control functions such as identity authentication,authorization deduplication and the update of access control policy.The outsourced data was only deduplicated with the authorized users,and the unauthorized users couldn’t obtain any data information.CP-ABE and the partition of the ElGamal private key were used to update the access control policy of data.Self-control objects was used to encapsulate user’s data and its access policy,providing authentication for data visitors and ensuring the access control policies enforced effectively.Security analysis and simulation results demonstrate that the proposed system enables data access control and executes efficiently.